Planning of the Underground Metro in the City of Samarkand (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
it is planned to annex the surrounding areas in order to include the city of Samarkand among the Million cities. Currently, a project has been developed on this. Under these projects, the city of Samarkand is divided into five regions. The transport sector is the most important sector in every developed city. In this regard, the issue of planning the underground metro in the city of New Samarkand should be considered in the future. This article will talk about the planning of the underground metro in the city of Samarkand.